DEMOCRATIC POSTGRADUATE STUDENT LEADERSHIP FOR A SUSTAINABLE LEARNING ENVIRONMENT - TSHELANE, MOLAODI (South African Journal of Higher Education, 2016)
Couched in the theory of communicative action as the theoretical framework, I document how the engagement of a South African university’s research team with the local school community facilitates the conversations and activities among its teachers, learners and parents towards the enhancement of learner performance in the study of Mathematics in a Grade 9 class. Theory of communicative action is understood as the democratic action based on the discursive rationality and validity of the arguments of individuals and/or groups of collectives. Because these communicative action decisions are not imposed, learners, teachers and parents have taken ownership of their own learning and this has resulted in improved performance. At the same time, we as researchers and participants have understood our democratic role and power in ensuring the success of this academic project. These findings indicate that a university, given its immense resources, including intellectual capital, can play a significant role in the creation of networked power, emancipatory knowledge, empowered subjectivities and spaces of solidarity which are the conditio sine qua non for good academic performance and sustainability of any democracy. Keywords: theory of communicative action, democracy, emancipatory knowledge, empowered subjectivities, higher education, networked power, spaces of flow, spaces of solidarity